Digital Model for Distance Education Management in Thai Supply Chain - Artaphon Chansamut (ExcelingTech, 2022)
The purposes of this study were to study and to evaluate digital model for distance education management in Thai supply chain . The samples are ten experts in the field of digital ,supply chain and curriculum . The data is analysed by means and standardized deviations. The paper result shows that a simulation consists of seven elements namely main elements, Suppliers, Manufacturer, ,finished product ,Customers, satisfaction and Return The assessment of a simulation using Black-Box testing. The paper findings revealed that a simulation is appropriate at the high which mean that Digital model for distance education management in Thai supply chain could be applied in support the tasks